Violence and invisibility: a collective case study on suicide among Emberá Indigenous youth in the Colombian Pacific - Rodríguez, Pedro E.; Pantoja-Santander, Ayda; Sapene, Alejandra; Cisneros, Cástulo (Frontiers in Education, 2025)
Ethnic minorities are exposed to greater risks of mental health problems than other groups, intensified during specific developmental periods by gender, psychosocial factors, racism, stigmatization, and social exclusion. In Colombia’s Pacific region, the Emberá Indigenous population has experienced a significant number of youth suicides in recent years, described as a “suicide epidemic.” This study aimed to deepen the understanding of suicide among Emberá youth by analyzing its characteristics, the institutional and professional strategies addressing it, and the processes of institutional racism and social exclusion at play. A collective case study approach was applied, drawing on primary and secondary sources, including interviews and a documentary review of 76 materials, to provide a contextualized understanding of suicide incidence in the Chocó region and to inform future educational, community, and activist actions. Findings indicate that suicidal behavior in this group has distinctive characteristics requiring approaches that go beyond nominal cultural sensitivity, engaging directly with lived realities and structural conditions. Current strategies reveal significant weaknesses, particularly in coordination and in adopting intersectional perspectives to address multi-problematic contexts. Results also highlight the impact of racism and exclusion on the emotional experiences of Emberá youth, expressed through both institutional discrimination and internalized racism. The study concludes by proposing the strengthening of institutional racism and psychosocial exclusion as analytical tools for addressing violence and invisibility in suicide cases, while emphasizing future pathways for action, particularly the active participation of young people in the design, implementation, and monitoring of protective strategies against suicide risk.